Ameloblastoma and keratocyst hybrid odontogenic lesion in a patient with Gorlin-Goltz syndrome with multiple keratocysts: case report - Ponzoni, Deise; Gaiger de Oliveira, Márcia; Pletsch Furlanetto, Amália; Puricelli, Edela (Clinical and Biomedical Research, 2024)
Hybrid odontogenic lesions combine characteristics of two or more lesions in a single site, and are considered a rare condition. The occurrence of this lesion in a patient with Gorlin-Goltz syndrome is even less common. Since the condition has variable clinical aspects and multiple imaging characteristics, histopathological examination is important for the definitive diagnosis of the lesion. This article reports the case of a patient with Gorlin-Goltz syndrome, with multiple odontogenic keratocysts in the mandible and maxilla and presence of an ameloblastoma and keratocyst hybrid odontogenic lesion. Distinct areas with histological patterns characteristic of the cyst and tumor were observed in the same lesion. This unusual but still possible diagnosis should be considered by pathologists and oral-maxillofacial surgeons in the evaluation, diagnosis and treatment of patients with syndromes characterized by odontogenic lesions.